1997
DOI: 10.1148/radiology.202.3.9051046
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation abnormalities in obstructive airways disorder: detection with pulmonary dynamic densitometry by means of spiral CT versus dynamic Xe-133 SPECT.

Abstract: PDD by means of spiral CT is acceptable for the detection of ventilation abnormalities in obstructive airways disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Moreover, bi-and unilateral changes associated with BOS could be detected with prolongedwashout images. Clearance of 133 Xe is reported markedly prolonged in obstructive airways disorder [5] and 133 Xe SPECT images frequently showed more extensive 133 Xe 1 3 retention than the spread of lesions visible on chest CT, even in lungs without any CT abnormalities [11,12]. Prolonged-washout images have been noted on lung fi elds in 133 Xe ventilation scan in two cases after bone marrow transplantation, indicating chronic obstructive lung disease [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bi-and unilateral changes associated with BOS could be detected with prolongedwashout images. Clearance of 133 Xe is reported markedly prolonged in obstructive airways disorder [5] and 133 Xe SPECT images frequently showed more extensive 133 Xe 1 3 retention than the spread of lesions visible on chest CT, even in lungs without any CT abnormalities [11,12]. Prolonged-washout images have been noted on lung fi elds in 133 Xe ventilation scan in two cases after bone marrow transplantation, indicating chronic obstructive lung disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary washout study with 133 Xe gas is widely used to detect regional changes in ventilation for both large and small airways. Recent studies have demonstrated the utility of 133 Xe lung ventilation scintigraphy in the evaluation of small airway disease, including BOS following lung transplantation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Main drawbacks are the limitations in spatial and temporal resolution. Improved anatomical detail is offered by cross-sectional images (single photon emission computed tomography (SPECT)) with slice thickness of 15 mm, and it has been shown to correlate well with lung function parameters in patients with emphysema [7,8]. Highly sophisticated nuclear medicine techniques for ventilation imaging make use of positron emission tomography (PET) with short half-live (17 s to 2 h) isotopes (Nitrogen-13 ( 13 N), Oxygen-15 ( 15 O), 19 Ne), Carbon-11 ( 11 C) [9].…”
Section: Nuclear Medicinementioning
confidence: 99%
“…Hypoventilated lung areas caused by expiratory obstruction are demonstrated by paired scans during an inspiratory and an expiratory breath-hold [13]. By using dynamic multirotation CT (spiral CT without table movement), however, a calculated temporal resolution of 100 ms can be achieved in a single slice [7,14]. A dynamic study of the whole lung is not possible, even though new technical developments (multislice spiral CT) will enable coverage of the whole lung within approximately 5 s. Postprocessing algorithms have been developed to derive functional information from CT datasets, such as density and area measurements, emphysema index, volumetry of ventilated airspaces, and diaphragmatic dimensions [15 -18].…”
Section: Computed Tomographymentioning
confidence: 99%
“…Dynamic 133 Xe gas single photon emission computed tomography (SPECT) is a useful tool in quantification of regional ventilation on cross-sectional lung planes in chronic obstructive pulmonary diseases (COPDs) [1][2][3][4][5][6][7][8][9][10]. The process of 133 Xe gas washout can be divided into the initial, rapid, washout phase, which mainly reflects rapid emptying of 133 Xe gas from the relatively large airways, and the late, slow, washout phase, which reflects the slow elimination of 133 Xe gas via the smaller airways at the level of the terminal bronchioles and alveolar air spaces [3][4][5]10,11].…”
Section: Introductionmentioning
confidence: 99%